Comparing the Effect of Rose Drop, Ginger, and Cinnamon on Sexual Function in Depressed Women with Sexual Dysfunction - Sheida Shabanian; Mahtab Ebrahimbabaei; Parvin Safavi; Masoud Lotfizadeh (Pharmacognosy Research, 2018)
Background: Sexual dysfunction is caused by multiple anatomical, physiological, medical, and psychological factors. Many studies have shown the efficacy of herbal remedies on increasing libido and sexual function. This study aimed to evaluate and compare the effects of three herbs of ginger, cinnamon, and rose on sexual function of depressed women with low sex drive. Materials and Methods: This randomized double‑blinded clinical trial was conducted on 140 depressed women with sexual dysfunction who were divided into four groups receiving oral drops of rose, ginger, cinnamon, or placebo. The information about the two variables of sexual function and depression were collected by Female Sexual Function inventory questionnaire and Beck Depression Inventory, respectively. Data were analyzed using Chi‑square, Wilcoxon signed‑rank test, Kruskal–Wallis test, and Pearson correlation coefficient. Results: The mean scores of sexual dysfunction and depression were significantly improved in the three groups after treatment (P < 0.05) so that sexual dysfunction score in placebo group had the lowest rate of improvement with the mean of 1.55 ± 0.44 and in ginger group had the highest improvement rate with the mean of 4.04 ± 1.07. Depression in placebo group had the lowest improvement rate with the mean of 3.71 ± 1.94 and in cinnamon group had the highest rate of improvement with the mean of 6.29 ± 1.57, but there was no significant difference between the four groups (P > 0.05). The factors such as received treatments with impact factor of 0.723 and age with impact factor of 0.170 had direct relation and depression with impact factor of −0.078 had reverse relation to sexual performance improvement (P < 0.05). Conclusion: Herbal medicines, except for their positive impacts on sexual function, may have positive but minor effects on depression.
Keywords: Cinnamon; Depression; Ginger; rose; Sexual desire